Community college first-year business student online course motivation - Johnson, Roy (Kansas State University, 2012)
The purpose of this case study was to explore the online learning environment through the experiences of the individual learner and to gain more insight into the elements of Business online courses, as framed by the Keller ARCS Model of Motivation. This study explored the following three Research Questions: 1. How do undergraduate first-year Business students perceive online course elements as being motivational? 2. How do the online courses that Business students perceive as being motivational use the Keller ARCS Motivational Model? 3 How do exemplary online Business faculty use the Keller ARCS Motivational Model in online instruction? The population was students enrolled in first-year for-credit online classes taken during the Fall 2010 semester in a Midwestern community college. A sample of required Business online sections was purposively selected in order to investigate Business student motivation. The participants in this study were 18 first-year Business students enrolled in Business courses. Based on student interviews, the instructors of the three courses that were most often nominated by students as being most motivational were interviewed. Interviews of students and instructors were conducted at the end of the Fall 2010 semester. Seven themes were identified for Research Question 1: 116 units for theme “Course Communication,” 83 units for theme “Course Requirements,” 71 units for theme “Grades,” 60 units for theme “Course Organization,” 50 units for the theme “Learning Online,” 48 units or the theme “Course Element Availability,” and 46 units for the theme “Track Course Progress.” For Research Question 2, the ARCS model categories were used as a framework for understanding and interpreting student motivation: “Attention,” “Relevance,” “Confidence,” and “Satisfaction.” The components of the Keller ARCS themes were then analyzed according to the components that students perceived as being most motivational. The ARCS Themes found were: 31 units for theme “Satisfaction,” 25 units for theme “Relevance,” 24 units were found for theme “Confidence,” and 20 units were found for theme “Attention.” The significant theme findings were: The Satisfaction theme was found to include practice prior to graded activities. The Relevance theme was found to include the use of “choices” as a key motivational component to what was perceived as being relevant. The Confidence theme was found to include a progression in difficulty of activities and access to review and practice new material. The Attention theme was found to include variability of instruction and course elements. To answer Research Question 3, faculty interviews focused specifically on the Keller ARCS Motivational Model and components. The ARCS themes found were: 36 units for theme “Confidence,” 25 units for theme “Relevance,” 24 units for theme “Satisfaction,” and 22 units for theme “Attention.” The significant findings from the themes were: The Confidence theme was found to include providing key information upfront to students. The design of the course must allow for student success and become progressively more difficult for students. Also, the time and effort required to complete activities should be provided to students. The Relevance theme was found to include the use of “choices” and to relate the course to the student’s situation as key motivational components. The Satisfaction theme was found to include negative consequences that are handled within the course, and practice that offers immediate feedback. The Attention theme was found to include students asking students questions within the course. Recommendations for further studies included a qualitative study to uncover how online Business students are motivated in their second and later years and a study to understand student motivation through various settings and technologies used in learning management system course elements.
Keywords: Online; Motivation; Education, Community College (0275); Education, Technology (0710)